Pendampingan dan Pemeriksaan Kesehatan Masyarakat Desa Terong Tawah, Kabupaten Lombok Barat: Investasi Vital dalam Kesehatan Masyarakat: (Community Health Assistance and Examination in Terong Tawah Village, West Lombok Regency: Vital Investment in Community Health) - Lalu Adiyatma Taopikul Hadi; Junaidin; Musparlin Halid; Rian Wahyul Ikhtiar; Muhammad Munawir Gazali; Adriyan Suhada; Beny Binarto Budi Susilo (Prodi Tadris IPA Biologi UIN Mataram, 2024)
Health check-ups play an important role in maintaining and improving the health of individuals, especially in rural communities such as Terong Tawah Village. These health checks are not only to diagnose diseases, but also to prevent diseases and improve overall health. The purpose of this activity is to provide an understanding of the importance of health checks for residents in Terong Tawah Village as a Vital Investment in Public Health. The method used in the implementation of this activity is a collaboration between lecturers and students of Politeknik Medica Farma Husada Mataram with Community Health Centre (CHC) officers who can increase the effectiveness of health checks in Terong Tawah Village, Labuapi District, West Lombok Regency, West Nusa Tenggara in January 2024. Blood pressure and blood sugar checks play an important role in maintaining good health, preventing chronic diseases, and improving the overall well-being of the community. By emphasizing the importance of monitoring these vital signs, individuals can take proactive steps to achieve better health outcomes, while community-wide screening initiatives can have a positive impact on public health. Prioritizing regular check-ups for blood pressure and blood sugar is crucial to promoting a healthier society. As such, increasing public awareness of blood pressure and blood sugar levels is critical to improving overall health and well-being. Education, early detection, and proactive management are key components in the fight against hypertension, diabetes, and their associated complications.